Role of Novel Multidrug Efflux Pump Involved in Drug Resistance in Klebsiella pneumoniae - Srinivasan, Vijaya Bharathi (Public Library of Science, 2014)

(untitled)
BACKGROUND: Multidrug resistant Klebsiella pneumoniae have caused major therapeutic problems worldwide due to the emergence of the extended-spectrum β-lactamase producing strains. Although there are >10 major facilitator super family (MFS) efflux pumps annotated in the genome sequence of the K. pneumoniae bacillus, apparently less is known about their physiological relevance. PRINCIPAL FINDINGS: Insertional inactivation of kpnGH resulting in increased susceptibility to antibiotics such as azithromycin, ceftazidime, ciprofloxacin, ertapenem, erythromycin, gentamicin, imipenem, ticarcillin, norfloxacin, polymyxin-B, piperacillin, spectinomycin, tobramycin and streptomycin, including dyes and detergents such as ethidium bromide, acriflavine, deoxycholate, sodium dodecyl sulphate, and disinfectants benzalkonium chloride, chlorhexidine and triclosan signifies the wide substrate specificity of the transporter in K. pneumoniae. Growth inactivation and direct fluorimetric efflux assays provide evidence that kpnGH mediates antimicrobial resistance by active extrusion in K. pneumoniae. The kpnGH isogenic mutant displayed decreased tolerance to cell envelope stressors emphasizing its added role in K. pneumoniae physiology. CONCLUSIONS AND SIGNIFICANCE: The MFS efflux pump KpnGH involves in crucial physiological functions besides being an intrinsic resistance determinant in K. pneumoniae.